(untitled) (Bangladesh Journal of Pharmacology, 2015)
The aim of this study was to reveal the phytochemical constituents, antioxidant and antimicrobial activity of Ajuga orientalis. According to the antimicrobial results, the methanol extract of A. orientalis showed a MIC value of 312.5 µg/mL against the tested pathogenic bacterial strains. Anticandidal activity of extract was found as 156.3 µg/mL both against Candida albicans and C. parapsilosis strains. Whereas the extract was more effective against C. tropicalis with the MIC value of 78.1 µg/mL. The in vitro DPPH radical scavenging activity of the extract was determined as IC50=0.4 ± 0.02 mg/mL whereas the standard BHT IC50 was 0.01 ± 0.00 mg/mL. Trolox Equivalent Antioxidant Capacity (TEAC) of extract was determined 1.3 mM TEAC, while BHT, 1.9 mM TEAC.